Mapeamento de produtos no estado de Roraima com potencial para registro de Indicação Geográfica - Pelentir, Marli Gisiele da Silva Aquino (2019)
Within the historical context, Geographical Indications worldwide date back to antiquity. However, the first Brazilian Geographical Indication was granted in 2002, in Vale dos Vinhedos, in the state of Rio Grande do Sul. From that period, in Brazil, the Geographical Indications have been showing a gradual growth and showing relevant contributions. for the economy of the country. Starting to be considered strategic tools with a view to contributing to business competitiveness. Through them there is the possibility to add value to the product, increase safety for consumers and develop the region in which they operate. Another important factor related to Geographical Indications refers to the protection of the country's intangible assets. There are currently fifty-four Indications of Origin and twenty Denominations of Origin. However, the state of Roraima shows the lack of registration. Thus, this work aims to perform a product mapping in the state of Roraima with potential for the registration of Geographical Indication. As for the operational procedures, we used bibliographic, documentary and field research, and the research objectives were descriptive. The tool used was a previously structured interview with a qualitative and quantitative approach. Thus, there were eight products in the state of Roraima with potential for the registration of Geographical Indication. They are: Serra Grande Pineapple II; Banana produced in the municipality of Caroebe, known as Banana do Caroebe; Chestnut of the mawayána ethnicity, known as Wai-wai Chestnut; Yanomami Mushroom, known as the Yanomami Mushroom; Bean from the Flexal Indigenous Community in Uiramutã, known as Flexal Bean; Watermelon produced in Normandy / Bonfim; Roraima Sun Meat Paçoca; and, Clay Pot of the Raposa Serra do Sol I indigenous community.